Preoperative Embolization for Skull Base Meningiomas - Suzuki, Kensuke (J Neurol Surg B Skull Base, 2017)
The results of preoperative embolization for skull base meningiomas were retrospectively evaluated to confirm the efficacy of this procedure. Skull base meningiomas that were treated with preoperative embolization were evaluated in 20 patients. The occluded arteries, embolic materials, treatment time, excision rate, neurologic manifestations, and complications were analyzed. The embolic material was 80% liquid, 30% coils, and 15% particles. The surgery was normally completed within 3 to 5 hours. Blood loss was normally approximately 250 mL, excluding four patients having the following conditions: malignant meningioma, a large tumor located on the medial side of the sphenoidal ridge, the petroclival tumor, and infiltrated tumor into the sigmoid sinus. The mean excision rate was 90%, achieving a Simpson grade III, but 10% were graded as Simpson grade IV. No permanent complications due to the preoperative embolization occurred. No neurologic symptoms occurred after excision. Current cerebral endovascular treatment is sophisticated, and the complication rate has markedly decreased. Although it was impossible to compare directly with or without operative embolization, preoperative embolization should be actively used as part of the treatment for this benign tumor, with better understanding of dangerous anastomosis.